2000
DOI: 10.1099/00221287-146-1-65
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Bacillus subtilis extracellular proteins: a two-dimensional protein electrophoretic study The SWISS-PROT accession numbers for the N-terminal amino acid sequences reported in this paper are: P00691 for AmyE; P54507 for CotN; O07921 for Csn; P09124 for Gap; P26901 for KatA; P39116 for Pel; P39824 for PenP; P54375 for SodA; P29141 for Vpr; Q07833 for WapA; P54423 for WprA; P54327 for XkdG; Q45071 for XynD; P94421 for YclQ; O31803 for YcnM; O05512 for YdhT; O34952 for YflE; O06487 for Yfn

Abstract: To analyse the proteome of Bacillus subtilis extracellular proteins, extracellular protein samples were prepared from culture media (minimal medium containing 04 % glucose) of parental B. subtilis 168, a secA-temperature sensitive mutant and an ffh conditional mutant, and examined by twodimensional gel electrophoresis. Approximately 100 to 110 spots were visualized in a gel of B. subtilis 168 extracellular proteins. Over 90 % and 80 % of these disappeared in the absence of SecA and Ffh, respectively. Thirty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
2

Year Published

2000
2000
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 54 publications
7
120
2
Order By: Relevance
“…SecA-dependent Secretion of Overproduced LipA-The Secdependent pathway of B. subtilis can be regarded as the major route for protein secretion into the growth medium (2,39). Therefore, we investigated whether the Tat-independently secreted LipA was transported in a Sec-dependent manner.…”
Section: Different Effects Of Tatc Mutations On the Extracellular Accmentioning
confidence: 99%
See 1 more Smart Citation
“…SecA-dependent Secretion of Overproduced LipA-The Secdependent pathway of B. subtilis can be regarded as the major route for protein secretion into the growth medium (2,39). Therefore, we investigated whether the Tat-independently secreted LipA was transported in a Sec-dependent manner.…”
Section: Different Effects Of Tatc Mutations On the Extracellular Accmentioning
confidence: 99%
“…Proteomic Evaluation of Sec-dependent Protein SecretionPrevious proteomic studies by Hirose et al (39) suggested that the secretion of the majority of extracellular proteins by B. subtilis is strongly SecA-dependent. However, the interpretation of these results was complicated by the fact that a temperature-sensitive secA mutant strain was used, which stops growing and dies upon temperature upshift.…”
Section: Different Effects Of Tatc Mutations On the Extracellular Accmentioning
confidence: 99%
“…Activities were determined using (1) , spectrophotometric; (2) , pH-stat; (3) , monolayer assays. the triacylglyceride tricaprylin (C8:0).…”
Section: Bacillus Lipases Have An Unusual Consensus Pentapeptidementioning
confidence: 99%
“…was about 10% for each given value. Activities were determined using the following assays, (1) , pH-stat; (2) , UVspectrophotometric; (3) , fluorescent; (4) , monolayer; (5) , spectrophotometric.…”
Section: Three-dimensional Structures Of Lipa and Lipbmentioning
confidence: 99%
See 1 more Smart Citation